Analisis Kontribusi Pajak Hiburan Terhadap Pendapatan Asli Daerah Kota Cimahi - Rahmawati, Rani; Anita, Dian (Rifa'Institute, 2022)
In a region, leaders are required to work together in order to generate a source of income for the region itself and the community in the form of regional original income. Cimahi City is a city that is trying to optimize its regional income. Based on data obtained from the Regional Revenue Management Agency, in the last few years, from 2016-2020 the entertainment tax payer in Cimahi City has increased. The increase in entertainment tax payers in Cimahi City is something that can increase local revenue in Cimahi City. The purpose of this study was to determine the contribution of entertainment tax to Cimahi City's Original Regional Revenue, the factors that caused the target not to be achieved, the effectiveness of entertainment tax revenues and the strategies used to increase entertainment tax revenues. The method used in this research is a qualitative research method. Researchers are interested in taking this discussion because in 2020 entertainment tax revenue in Cimahi City is very low. The conclusion of this study is that the contribution of entertainment tax to Cimahi City's Original Regional Revenue is very low. However, entertainment tax revenue from 2016 to 2020 is always effective every year. Except in 2020 it is not effective. And every year it always achieves the target except in 2018 and 2020. Because it does not reach the target in 2018 and 2020, the Cimahi City BAPPENDA applies several strategies to increase entertainment tax revenues.